A case study on the data management and preservation practices of the research laboratories of the Philippine Nuclear Research Institute Gerard Paul SD. Pascual ; Mary Grace P. Golfo-Barcelona, adviser. - Pascual, Gerard Paul SD (School of Library and Information Studies, University of the Philippines Diliman, 2018)
The study looks into the data management and preservation policies and practices employed by the researchers of the Atomic Research Division of the Philippine Nuclear Research Institute, based on data management practices in foreign countries and through the Open Archival Information System functional model as background.